تقييم أداء القطاع السياحي وتأثيراته على الاقتصاد الجزائري : خلال الفترة 2008 - 2014 - السبتي، وسيلة Alsebti, Waselah; صحراوي، محمد تاج الدين Sahrawi, Mohammed Tajulddin (جامعة العربي بن مهيدي أم البواقي - مخبر المالية، المحاسبة، الجباية والتأمين, 2017)
Tourism is one of the most important subjects that have taken place and continue to occupy society at these different levels (economic, administrative, social, etc.), and at the level of all sectors. \ The tourism sector is a key sector in some countries and an alternative in other countries, tourism has a very significant impact in the developed countries, which is highlighted by the figures and statistical data of international tourism. From this point of view, Algeria has been keen to organize the tourism sector in accordance with professional standards and strategies and their application and make it an alternative to the hydrocarbon sector.
يعتبر موضوع السياحة من أهم المواضيع التي شغلت ولا تزال تشغل المجتمع بمستوياته المختلفة (الاقتصادي، الإداري، الاجتماعي..)، وعلى مستوي جميع القطاعات. ويعتبر القطاع السياحي قطاع أساسيا في بعض الدول وبديلا أو ناشئا في دول أخرى، فآثار السياحة في الدول المتقدمة جد قوية وهذا ما تثبته الأرقام الإحصائية ومعطيات السياحة الدولية. ومن هذا المنطلق حرصت الجزائر على تنظم قطاع السياحة وفق المعايير والاستراتيجيات المهنية وتطببيها وجعله كأحد البدائل لقطاع المحروقات.
Keywords: السياحة; الجزائر; الإيرادات السياحية; الاقتصاد الجزائري